KRISIS EKSISTENSI PENGGUNAAN BAHASA JAWA DALAM KELUARGA JAWA (STUDI KASUS DI DUSUN SIROTO KELURAHAN SUSUKAN KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG) - Hidayah, Nur Fitri (Solidarity: Journal of Education, Society and Culture, 2013)
One of the diversity of local languages ??in Indonesia is Javanese. Java community especially families Java language using the Java language as a mother, to communicate on a daily basis. Now this archipelago language development in this area of ??language began with an identity crisis with the introduction of the changes. This study used a qualitative approach. Research sites in the hamlet Siroto Ungaran District East Village Susukan Semarang regency. Subjects in this study were parents, children, community leaders and prominent educators. Data collection techniques used were observation, interviews, and documentation. The validity of the data used is the technique of triangulation data. Data analysis techniques, namely data collection, data reduction, data presentation, and conclusion or verification. The results showed that the existence of crisis among families use the Java language in Hamlet Siroto ngoko the use of the Java language to parents, rather than the communication code in the Java language into Indonesian, and changes in the use of kinship terms. The crisis caused by the existence of the Java language using the Java language is less socialization by parents and the use of the Indonesian language for communication within the family and Traffic lacking in Javanese. In addition, the influence of the language of the neighborhood, the neighborhood association and language television .. Impact will be generated are Java language will be minor and endangered species as well as upload and reduced-ungguh attitude towards parents.